Furniture fundamentals - casework : techniques and projects for building furniture and cabinetry - Francis, Scott (Furniture fundamentals, 2016)
"Mastering casework--essentially making boxes--allows you to create a wide variety of furniture from cabinets to bookcases to blanket chests. Within these pages, you'll find insight into various approaches to casework including face frames, frameless constructions and joinery options from simple to advanced. You'll learn the most used joinery techniques including rabbets, dados, dovetails and mortise-and-tenon. You'll gain insight into making boxes of all sizes from carcases to drawers, and hone your skills through 9 step-by-step furniture projects ranging from simple wall cabinets to beautiful chests of drawers. When you get right down to it, so many furniture forms start with building a box. This book is your guide to mastering this fundamental aspect of furniture making"--Page 4 of cover